Management and Governance Issues Discussion in Vietnam and Asian Pacific Corporate Governance Standards - Dinh, Trung Van; Duong, Phan Huy; Huong, Nguyen Thi Thuy; Tha, To Hien (International Journal of Membrane Science and Technology, 2023)
This paper mainly concentrates on empirical research for findings in Management and Governance Issues Discussion in Vietnam and Asian Pacific Corporate Governance Standards. First, it comes up with findings on corporate governance subjects in the post-crisis and post-scandal time. It found out that companies in these periods have certain corporate governance issues such as how to better organize an information disclosure system. Second,this paper provide with a short summary of evaluation of current corporate governance principles in these four countries which can enable corporations to seek and to compare to their current codes. Last but not least, Vietnam SSC also informed set of documents was developed with technical support from the International Finance Corporation, a member of the World Bank Group, and the support of the Swiss State Department of Economic Affairs (SECO), and includes the following criteria: standards higher than the minimum legal requirements, encouraging businesses to move towards international best practices.